DIGITAL TRANSFORMATION, BUSINESS MODELS, MARKETING STRATEGIES, AND SUSTAINABLE PERFORMANCE IN MSMES: A SYSTEMATIC LITERATURE REVIEW - Januar Habibi Mahsyar; Faishal Rahimi; Ilham Akbar; Neng Evi Kartika (Universitas Kuningan, 2026)
This systematic literature review examines how digital transformation reshapes small and medium enterprises (SMEs) through three lenses: business model reconfiguration, digital marketing strategy, and sustainable performance. Following PRISMA 2020, searches were conducted on 5 January 2025 across Scopus, Web of Science, Garuda, and SINTA using Boolean strings limited to titles, abstracts, and keywords. Of 312 records, 240 remained after deduplication, 75 underwent full-text assessment, and 28 articles published between 2018 and 2025 met the inclusion criteria (18 Scopus-indexed international and 10 SINTA-accredited Indonesian). Two reviewers screened independently (Cohen's kappa = 0.78 and 0.81), resolving disagreements through discussion; methodological quality was appraised using the Mixed Methods Appraisal Tool. The protocol was not registered, a limitation. Findings indicate that digital transformation drives a shift toward platform-based, data-enabled business models, mediated by dynamic capabilities and business model innovation. Digital marketing strategies, social media engagement, content-based storytelling, marketplace integration, and customer relationship management, act as a strategic capability converting digital adoption into measurable market performance. The link between digital transformation and sustainable performance across economic, social, and environmental dimensions is positive but conditionally moderated, particularly in resource-constrained contexts such as Indonesian MSMEs. The study proposes an integrative conceptual framework and practical recommendations for managers and policymakers.